Characterisation of passive intermodulation in passive RF devices with X-parameters - Kozlov, Dmitry S.; Shitvov, Alexey P.; Schuchinsky, Alexander G. (2014 Loughborough Antennas and Propagation Conference (LAPC), 2014)
A novel approach to the modelling of passive intermodulation (PIM) generation in passive components with distributed weak nonlinearities is outlined. Based upon the formalism of X-parameters, it provides a unified framework for co-design of antenna beamforming networks, filters, combiners, phase shifters and other passive and active devices containing nonlinearities at RF front-end. The effects of discontinuities and complex circuit layouts can be efficiently evaluated with the aid of the equivalent networks of the canonical nonlinear elements. The main concepts are illustrated by examples of numerical simulations of PIM generation in the transmission lines and comparison with the measurement results.